Persepsi Mahasiswa Program Studi Pendidikan Bahasa dan Sastra Indonesia terhadap Mata Kuliah Arab Melayu - Hasnah Faizah; Anisa Putri Rahayu; Finie Lestari (Universitas Maritim AMNI Semarang, 2024)
This research is aimed at digging the perception of students of the Indonesian Language and Literature Education Studies Program FKIP University of Riau towards Malay Arabic courses. The study used a qualitative descriptive approach to the population of students of the Indonesian Language and Literature Education Studies Program with a sample of 25 respondents. The results revealed significant variations in students' perceptions of Malay Arab courses at Riau University. Although most students indicate a good level of previous interaction with the material, there are differences in views on the relevance of the course. In general, students responded positively to teaching methods and considered these courses to have a positive impact on the development of communication skills and an understanding of local history and culture. Nevertheless, continuous evaluation is needed to understand and respond to the diverse needs of students. Student suggestions, such as the integration of courses in various majors and increased use of media, provide valuable insights for future course improvements. The conclusion emphasizes the importance of adaptability and responsiveness to student feedback inining the quality of learning of Malay Arab courses.